IMPLEMENTASI PENERAPAN PASAL 38 UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA SEBAGAI UPAYA PERLINDUNGAN HUKUM KARYA SENI BATIK - Agustina Balik (Faculty of Law, Universitas Pattimura, 2015)
Batik has a strong background with the nation and the people of Indonesia in all fields and forms of culture and everyday life. Copyright Act No. 28 of 2014 Section 38 (1) which stipulates that copyright to the traditional art of batik in Indonesia, the copyright is held by the state. During the system has not been formed for the protection of Traditional Knowledge, clearly, the whole intellectual creations are based on tradition can refer to the provisions in the UUHC. The protection provided is not confined to the art of batik, but also for folklore and all works of popular culture that became property of the people Indonesia. Indonesian government to provide legal protection to folklore including the art of batik to prevent monopolistic practices or the commercialization and actions damaging or commercial use without permission of the Republic of Indonesia as a copyright holder. This effort is intended to avoid any action that could damage the foreign party of Indonesia's traditional cultural values.